A comparative study between ProSeal laryngeal mask airway and endotracheal tube for ease of insertion and haemodynamic changes in patients undergoing laparoscopic cholecystectomy under general anaesthesia - Patodi, Veena; Singh, Maina; Sethi, Surendra K.; Depal, Vini N.; Jain, Neena; Kumar, Vijay (International Journal of Research in Medical Sciences, 2016)
Background: The endotracheal tube is considered a gold standard for providing a safe and effective glottic seal, especially for laparoscopic procedures under general anaesthesia. However, haemodynamic pressor responses associated with its use might be detrimental. The ProSeal LMA minimizes this response without compromising the airway with lesser incidence of complications. The aim of this study was to compare ProSeal LMA and Endotracheal tube with respect to intra-operative haemodynamic responses and ease of insertion of device and nasogastric tube in patients undergoing laparoscopic surgeries under general anaesthesia. Methods: This prospective randomized study was conducted on sixty patients, aged 20-60 years; of ASA grade 1 or 2, 30 in each group, posted for laparoscopic cholecystectomy under general anaesthesia. After induction with propofol and neuromuscular blockade with rocuronium, PLMA or ETT was inserted. The haemodynamic responses and insertion time of device and nasogastric tube were noted. Postoperative complications, if any were also noted. Results: The mean time of insertion of PLMA was 37.40±16.09 seconds and for intubation (ETT) was 31.17±20.89 seconds which was statistically not significant (P >0.05). The mean time of insertion of nasogastric tube was 18.84±6.84 seconds in PLMA group and 73.00±71.06 seconds in the ETT group which was highly significant, (P <0.001). There was a statistically significant increase in the heart rate(HR),systolic blood pressure (SBP),diastolic blood pressure (DBP) and mean arterial pressure (MAP) at intubation that persisted till 5 minutes of intubation and also at the time of extubation in ETT group, (P <0.05). However, the haemodynamic parameters remained comparable to baseline values, after insertion of ProSeal and at its removal in PLMA group (P>0.05). Conclusions: ProSeal LMA proved to be a suitable alternative to endotracheal tube for airway management with stable haemodynamics in patients undergoing laparoscopic cholecystectomy under general anaesthesia.